Classroom Interaction Research: The State of the Art. Issue 3 (3rd July 2019) - Gardner, Rod
ABSTRACT: This article reviews classroom interaction research that uses Conversation Analysis and other interactional approaches. Schools as social institutions are crucial in the modern world, preparing people to live in highly complex societies, from preschool through to tertiary education and beyond. Although classrooms vary significantly internationally, research has focused mainly on schools where classes have a teacher in charge of varying numbers of students. While most research has been on English as an additional language (EAL) and other second language classrooms, this article will also review work on classrooms where other school subjects are taught, classrooms with younger children, as well as CA work that focuses on learning. Data reported are in English.